PEMBELAJARAN BAHASA JERMAN BERORIENTASI KARIR - Ida Costansa Tamaela; Carolina Lestuny; Grietje Hanna Kunu (German für Gesellschaft (J-Gefüge), 2023)
Abstract Foreign languages have become a necessity that must be mastered for a career. German as a foreign language taught at the high school/vocational school level provides opportunities to develop careers at an international level. This is proven by the increasing number of resources who have pursued careers in Germany with the skills or competencies they possess. Unfortunately, not everyone has and understands this. This activity from the German Language Education Study Program aims to provide knowledge and assistance to German language teachers to understand the importance of mastering German to develop their skills. The methods used in this activity are surveys, lectures, questions and answers, and interactive dialogue concerning predetermined themes. The results obtained from this activity are that teachers and students understand career-oriented German language learning. Teachers can adapt learning themes to students' future work needs. Teachers can make variations in German language learning in the classroom. Besides that, students can gain insight into the theme as well as hear direct experiences from alumni who currently live in Germany. Keywords: German language, career oriented, SMKN 6